The Effect of Timber Harvesting on Fluctuation of Peat Water Level and Subsidence of Peat-Soil Surface - Sona Suhartana; Yuniawati Yuniawati (Center for Journal Management and Publication, 2018)
A goal of timber harvesting is to increase timber production through removing the timber from the forest using some harvesting techniques. A peatland is a fragile ecosystem and may degraded easily. Logging activities may adversely affect the soil compactness that disrupt the peat drainage system as well as cause subsidence, then ultimately may cause the sustainability of peat. This study was focused on examining the effect of timber harvesting acivities in peat forest plantation. The peatland damage may in the form of increased bulk density, water level fluctuations of peat (TMA), subsidence, irreversible and carbon emissions. The objective of the study is to find out the effect of timber harvesting in peatland plantations to peat water fluctuations and subsidence. The results showed that logging activites caused : (1) The average of water table and water level are about 1.03 and 0.967 m; and (2) Subsidence about -8 to -12.5 cm with the average is -11.0 cm.